Combining Transjugular Intrahepatic Portosystemic Shunt with Balloon-Occluded Retrograde Transvenous Obliteration or Augmenting TIPS with Variceal Embolization for the Management of Gastric Varices: An Evolving Middle Ground? - Saad, Wael E. (Seminars in Interventional Radiology, 2014)
The American College of Radiology Appropriateness Criteria Committee on interventional radiology has recently recognized balloon-occluded retrograde transvenous obliteration (BRTO) as a viable alternative to transjugular intrahepatic portosystemic shunt (TIPS) in certain anatomic and clinical scenarios for the management of gastric varices. However, it did not define these particular scenarios where BRTO would be a viable alternative. With the increased practice of BRTO in the United States, a debate ensues in the United States and Europe whether BRTO or TIPS should be the primary endovascular procedure of choice for gastric varices. From a conservative standpoint, BRTO is reserved for patients who are not TIPS candidates, while other institutions leave the decision to operator preference and “favorable anatomy” for either procedure. To add to the debate, there is a heightened interest in the improved efficacy of variceal embolization (metallic/bland embolization) concurrent with TIPS compared with TIPS without embolization, and a recent article describing a combination of TIPS and BRTO that demonstrated impressive results superior to BRTO or TIPS alone. This article discusses the most recent outcomes of TIPS and embolization of gastric varices as well as combining BRTO and TIPS.
Keywords: TIPS; BRTO; portal hypertension; interventional radiology